The Impact of Giving Sports Massage and Active Recovery on Lactate Recovery - Mohamad Brilian; Surdiniaty Ugelta; Pipit Pitriani (STKIP Muhammadiyah Kuningan, 2021)
This study aimed to determine the difference in the effect of the sports massage recovery method and active recovery on the lactate levels of wrestling athletes. This research sample consisted of 6 female athletes in West Java PON wrestling divided into two groups, namely the group that used sports massage and used active recovery. The analysis and data calculation results revealed that active recovery showed more significant results in reducing lactate levels (3.8 ± 0.54) compared to sports massage (2.6 ± 0.23).